Unique Experience of Mother's Parenting for Stunted Toddlers - Hidayah, Seventina Nurul; Fatimah, Okta Zenita Siti (Universitas Muhammadiyah Surakarta, 2024)
Introduction: The high prevalence of stunting is caused by suboptimal parenting practices. According to the Health Profile of Central Java Province in 2022, there were 830 children aged 0-5 years in the city of Tegal experiencing stunting. This figure is distributed across 27 sub-districts, with Slerok being the most affected, with 133 cases reported. This research aims to describe maternal parenting practices towards stunted toddlers in Slerok Sub-district. Method: The qualitative research method with a phenomenological approach was employed. Data were collected through in-depth interviews, observations, and document analysis. The informants consisted of 6 mothers with stunted toddlers as the main informants, along with 2 supporting informants, namely the Posyandu Cadre in Slerok Sub-district and the nutrition officer at Slerok Community Health Center. Result: The findings revealed that not all mothers practiced early breastfeeding initiation, and some did not provide exclusive breastfeeding until the age of 2 due to perceived difficulty in weaning. Additionally, some informants often forgot to wash their hands before feeding their children due to household chores. Conclusion: It is hoped that health workers and Posyandu cadres can promote good parenting practices, especially for pregnant and lactating mothers in Slerok Sub-district. Pendahuluan: Tingginya prevalensi stunting disebabkan oleh pola asuh yang belum optimal. Berdasarkan Profil Kesehatan Provinsi Jawa Tengah tahun 2022, di Kota Tegal terdapat 830 anak usia 0-5 tahun yang mengalami stunting. Angka tersebut tersebar di 27 kecamatan, dengan Kecamatan Slerok menjadi kecamatan dengan jumlah kasus terbanyak yaitu sebanyak 133 kasus. Penelitian ini bertujuan untuk mendeskripsikan pola asuh ibu terhadap balita stunting di Kecamatan Slerok. Metode: Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan analisis dokumen. Informan terdiri dari 6 orang ibu balita stunting sebagai informan utama, dan 2 orang informan pendukung yaitu Kader Posyandu Kecamatan Slerok dan Petugas Gizi Puskesmas Slerok. Hasil: Hasil penelitian menunjukkan bahwa belum semua ibu melakukan inisiasi menyusu dini, bahkan ada yang tidak memberikan ASI eksklusif hingga usia 2 tahun karena dianggap sulit untuk menyapih. Selain itu, beberapa informan sering lupa mencuci tangan sebelum memberi makan anak-anak mereka karena pekerjaan rumah tangga. Kesimpulan: Diharapkan petugas kesehatan dan kader posyandu dapat mempromosikan praktik pengasuhan yang baik, terutama bagi ibu hamil dan menyusui di Kecamatan Slerok.